2011
DOI: 10.3855/jidc.1889
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum and intestinal parasitic co-infections in HIV-infected patients in Benin City, Edo State, Nigeria

Abstract: Introduction: Human co-infection with Plasmodium falciparum and helminthes is ubiquitous throughout Africa. This study aimed to determine the co-infections of Plasmodium falciparum infection in HIV and intestinal parasitic infections, and their immunological distribution, in Benin City, Nigeria. Methodology: A total of 2,000 stool specimens from HIV-positive patients and 500 controls (HIV-negative individuals) were examined for ova, cysts, or parasites using standard procedures. In addition, patients' blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Of the 8 parasites recovered, hookworm (75%) predominated, and this agrees with a previous report [10]. Previous reports from UBTH, ISTH and another tertiary hospital in a rural community of Edo State among HIV and non-HIV subjects indicated that Ascaris lumbricoides was the most prevalent intestinal parasites [12,[15][16][17][18][19]23]. Only one study among diabetic patients reported hookworm as the most prevalent intestinal parasites [9].…”
Section: Discussionsupporting
confidence: 86%
“…Of the 8 parasites recovered, hookworm (75%) predominated, and this agrees with a previous report [10]. Previous reports from UBTH, ISTH and another tertiary hospital in a rural community of Edo State among HIV and non-HIV subjects indicated that Ascaris lumbricoides was the most prevalent intestinal parasites [12,[15][16][17][18][19]23]. Only one study among diabetic patients reported hookworm as the most prevalent intestinal parasites [9].…”
Section: Discussionsupporting
confidence: 86%
“…P. falciparum, helminthes, and the HIV virus are endemic in sub-Saharan Africa making co-infection a reality. Akinbo et al have previously reported co-infections of P. falciparum and Ascaris lumbricoides in HIV-infected patients in Benin City, Nigeria [22]. In this study involving 2,000 HIV-infected patients that were examined from August 2007 to August 2009, we found that 25.2% of the enrolled individuals were positive for P. falciparum [15].…”
Section: Discussionmentioning
confidence: 60%
“…The prevalence of anemia observed was 45.26% and is an important cause of anemia among HIV-infected patients on HAART [15]. Both HIV and Plasmodium infections can lead to anemia independently [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Nigeria is such a setting, with holoendemic malaria in much of the country, a significant burden of helminth infections, and nutritional deficiencies secondary to poverty. [11][12][13] Though ZDV is part of the recommended first-line regimen, Nigerian ART guidelines recommend avoiding the use of ZDV or switching to another drug in persons having baseline haemoglobin values of less than 8 g/dL. 14 We conducted a retrospective cohort study of HIV-infected patients in rural north-central Nigeria to track changes in haemoglobin levels during the first year of therapy in patients initiating ZDV-based regimens, stratified by baseline haemoglobin level.…”
Section: Introductionmentioning
confidence: 99%